PELAKSANAAN BAURAN PROMOSI TIKET PENERBANGAN PADA PT. MENTARI LINTAS WISATA ( MELIWIS ) PEKANBARU - Willa Austrin; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Promotion is a way of communicating that is usually done in an organization that has the goal of attracting potential buyers to buy the goods and services being sold or offered. This study aims to determine the implementation of the flight ticket promotion mix at Pt. Mentari Cross Tourism (Meliwis) Pekanbaru. This study uses a qualitative method with a descriptive approach, the subject of this study is the Director. Data collection is done by interviews, observation, and documentation. Data analysis carried out in this study was data reduction, data presentation, and drawing conclusions. The results of this study are that the implementation of promotions is carried out through 5 (five) techniques which include Advertising (Advertising), Sales Promotion (Sales Promotion), Public Relations (Public Relations). Personal Selling, Direct Marketing. Keyword : Promotion mix, promotion technique, PT. Mentari Lintas Wisata